THE EFFECT OF PAYMENT GATEWAYS, DIGITALIZATION OF MSMEs, FINANCIAL LITERACY, AND VENTURE CAPITAL ON MSME PERFORMANCE. - Ananda, Diva Firma; Biduri, Sarwenda; Nurasik; Harianto, Wiwit (Universitas Airlangga, 2025)
MSMEs play an important role in economic development, overcoming the problem of poverty, and are able to provide employment opportunities. This research aims to determine the influence of payment gateways, digitalization of MSMEs, financial literacy, and business capital on the performance of MSMEs. This research uses a quantitative type of research using primary data. The population of this research is 14,410 MSME food and beverage actors in Sidoarjo Regency. Samples were taken using nonprobability sampling with a purposive sampling method and distributing questionnaires to a total of 99 respondents. The data analysis technique used in the research is multiple linear regression analysis with the help of the IBM SPSS version 23 test tool. The results of this research show that payment gateways, digitalization of MSMEs, financial literacy and venture capital have an influence on MSME performance